Born this way: Hippocampal neurogenesis across the lifespan. Issue 5 (12th July 2019) - Kozareva, Danka A.; Cryan, John F.; Nolan, Yvonne M.
Abstract: The capability of the mammalian brain to generate new neurons through the lifespan has gained much attention for the promise of new therapeutic possibilities especially for the aging brain. One of the brain regions that maintains a neurogenesis‐permissive environment is the dentate gyrus of the hippocampus. Here, new neurons are generated from a pool of multipotent neural progenitor cells to become fully functional neurons that are integrated into the brain circuitry. A growing body of evidence points to the fact that neurogenesis in the adult hippocampus is necessary for certain memory processes, and in mood regulation, while alterations in hippocampal neurogenesis have been associated with a myriad of neurological and psychiatric disorders. More recently, evidence has come to light that new neurons may differ in their vulnerability to environmental and disease‐related influences depending on the time during the life course at which they are exposed. Thus, it has been the topic of intense research in recent years. In this review, we will discuss the complex process and associated functional relevance of hippocampal neurogenesis during the embryonic/postnatal period and in adulthood. We consider the implications of hippocampal neurogenesis during the developmentally critical periods of adolescence and older age. We will further consider the literature surrounding hippocampal neurogenesis and its functional role during these critical periods with a view to providing insight into the potential of harnessing neurogenesis for health and therapeutic benefit. Abstract : In this review, we will discuss the complex process and associated functional relevance of hippocampal neurogenesis during the embryonic/postnatal period and in adulthood. We will further consider the literature surrounding hippocampal neurogenesis and its functional role during the adolescent, and the ageing stages of the lifespan with a view to providing insight into the potential of harnessing neurogenesis for health and therapeutic benefit.